The Role of Migrants in the Production of Tradeables and Non-tradables. The Case of Austria - Gudrun Biffl (Austrian Institute of Economic Research (WIFO), 2003)
Globalisation has been associated with increased international mobility of capital but less so of labour partly because of legal restrictions. In theory, labour mobility and trade are generally substitutes in respect of tradeable goods and services. There are, however, also instances of complementarity between migration and trade. The promotion of free trade and the regulation of migration suggest that trade rather than migration is the preferred instrument to promote economic growth. Empirical evidence suggests that not only political but also economic forces tend to promote international trade rather than migration in the current period of globalisation. In the course of the 1990s, labour mobility in western Europe lagged behind the growth in international trade of goods and services as industries employing a high proportion of migrants in the production of tradeable goods declined. Technological developments, the reduction in transport costs as well as catching up processes in the productive capacities of less developed trading partners, e.g., Central and Eastern European Countries (CEECs), resulted in a change in the composition of production of tradeable goods. However, the composition of migrant labour by industry and skills changed little, and labour mobility lost momentum. Thus, the transfer of production of goods and services to less developed countries, in the case of the EU, CEECs, contributed to the loss of momentum in demand pull migration. Recent developments especially in communications technology, tended to promote mobility of services rather than labour mobility. As long as capital, technology and managerial skills are mobile, labour may remain in the country of origin, e.g., the case of Indian computer programmers. Physical labour mobility remains necessary only where services are linked directly to the consumers, for example, nursing or tourist services, or where a particular type of labour is linked to direct capital investment, for example, highly skilled labour which moves with multinational companies ...
Keywords: 330; Migration; Tradeables; Migrants; Austria; Internationale Migration; Arbeitsmigranten; Handelbare Güter; Nicht-handelbare Güter; Österreich